Agile Governance in the Perspective of Public Services Through the Public Complaints Channel Handling People with Social Welfare Problems (PMKS) in South Jakarta - Rofiyanti, Eka; Dewantoro, Bastian; Agustina, Dwi; Rulandari, Novianita; Razikin, Khairur (Budapest International Research and Critics University, 2021)
This research is motivated by the increasing number of People with social welfare problems (PMKS), especially beggars and street children, so a response from various stakeholders is needed to overcome this as a form of social security protection for citizens. With the rapid development of technology, advances in information technology, and the potential for their use widespread; it opens opportunities for accessing, processing, and utilization of information in large volumes quickly and accurately. Also, it is to integrate the needs of the community by implementing channel community complaints through the system Citizen Relation Management (CRM) with the name Aplikasi Cepat Respon Masyarakat (Quick Response Community’s Application). The purpose of this research is to analyze government governance in providing public services through handling public complaints with social welfare problems (PMKS) in South Jakarta. The research method is descriptive research with a qualitative approach, which is further elaborated with secondary data from the play store, social media, or other news media. The data collection techniques were carried out through interviews, observation, and documentation data. The results of the study showed that the application of the public complaint channel through the system (Citіzеn Rеlаtіоn Management) as a form of Agile Governance seen from the 5 principles has been running quite well. It was because each principle has been implemented well even though some obstacles were still being faced. The use of public complaint channels should be re-socialized to the community, so the level of community participation in reporting problems in the surrounding environment can be maximized. In addition, from the point of view of service providers, the performance and capacity of service providers should be further improved so that the public complaint service channel can be utilized optimally